The symbolic use of cohort studies: redefining crime between diversion and "selective incapacitation" - Bettmer, Franz (Contemporary crises, 1990)
The societal definition of crime is eroding. As a consequence of this secular process the focus of interest among criminologists and the agents of the criminal justice system is widening towards the whole of society. A new definition of crime is emerging, based on the difference between dangerous career criminals and spontaneous one time offenders. This difference is determined in terms of personality and character types based on criminological ideas about the typical hard core criminal. Cohort studies provide the data and information to construct this ideal type.